Variabel-variabel yang Memengaruhi Status Bekerja pada Lansia Penyandang Disabilitas di Nusa Tenggara Timur Tahun 2022 - Saharani, Karima; Setiadi, Yaya (Politeknik Statistika STIS, 2024)
The percentage of elderly people in Indonesia continues to increase, which has an impact on increasing the elderly dependency ratio. Efforts to empower the elderly need to be made so that the addition of elderly people does not become a burden on the young population. Additionally, the health of elderly workers, particularly those with disabilities, must be considered due to their increased vulnerability. NTT, the province with the highest percentage of working elderly and the third highest percentage of people with disabilities in Indonesia in 2022, was chosen for this research. The study aims to identify variables affecting the employment status of elderly people with disabilities in NTT using descriptive and inferential analysis, specifically binary logistic regression. Results show that 21.94 percent of elderly people with disabilities are still working in NTT. Significant variables influencing their decision to work include age, cohabitation status, and type of disability.